Strategi Komunikasi Hubungan Masyarakat untuk Membangun Citra Positif Pemerintah Kabupaten Bima Bervisi “RAMAH” (Religius, Aman, Makmur, Amanah, Handal) - Sauki, Muhammad (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This paper discusses the public relations communication strategy of the Regional Government of Bima Regency with the vision of "RAMAH” (Religius, Aman, Makmur, Amanah, dan Handal) in building its positive image in the eyes of the public. This paper used descriptive-qualitative analysis, on how public relationofBima Regency builds a positive image to foster harmonious relations between government organizations and the community and prevent the occurrence of psychological barriers that may occur between them. Public relations is a management function that aims to bridge the gap between the organization and its internal and external stakeholders. All policies and whatever happens in the organization, managers of public relations must know it. As a spokesman for the government, the role of public relations in government circles is very important in building a positive image of the government. In the current era of openness, public relation has an important and strategic role to support the achievement of goals set by organizational management. In the context of development, many activities have been carried out by the public relation of the Bima Regency Government to form its positive image by conducting socialization, reporting by cooperating with online media, both local and national, to publish government programs and performance as a form of realization of the vision of "RAMAH”.